2017
DOI: 10.1007/s00701-017-3290-1
|View full text |Cite
|
Sign up to set email alerts
|

Using external lumbar CSF drainage to treat communicating external hydrocephalus in adult patients after acute traumatic or non-traumatic brain injury

Abstract: These findings indicate that ELD may be considered potentially effective in controlling ICP, remaining safe if a firm diagnosis of communicating external hydrocephalus has been made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 26 publications
0
36
0
2
Order By: Relevance
“…This is acute hydrocephalus and frequently requires an external ventricular drain (EVD). An alternative form of acute hydrocephalus, without ventricular enlargement, is 'external hydrocephalus' due to impairment of CSF absorption in Pacchionian granulations [1,2] when only the cranial subarachnoid space is enlarged. Different trials, especially recent decompressive craniectomy trials, have reported variable incidences of hydrocephalus post severe TBI, and the rate of reporting hydrocephalus as a complication of TBI varies between 0.7 and 50% [7][8][9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is acute hydrocephalus and frequently requires an external ventricular drain (EVD). An alternative form of acute hydrocephalus, without ventricular enlargement, is 'external hydrocephalus' due to impairment of CSF absorption in Pacchionian granulations [1,2] when only the cranial subarachnoid space is enlarged. Different trials, especially recent decompressive craniectomy trials, have reported variable incidences of hydrocephalus post severe TBI, and the rate of reporting hydrocephalus as a complication of TBI varies between 0.7 and 50% [7][8][9][10][11].…”
mentioning
confidence: 99%
“…In the late phase after TBI, patients can present with symptoms or signs similar to idiopathic normal pressure hydrocephalus (iNPH) resulting from impairment of CSF circulation in the subarachnoid space in response to the post-traumatic inflammatory process. The ventricles are enlarged but ICP remains normal [1][2][3]12]. Post-acute PTH could inhibit rehabilitation and be the main contributing factor to poor long-term outcome after TBI [13,14].…”
mentioning
confidence: 99%
“…El diagnóstico se basa en los siguientes elementos: alto índice de sospecha cuando se presenta una patología como las citadas; presencia de HIC con cisternas presentes y conservación del buffer espacial, o los métodos no invasivos (medida ultrasonográfica de la vaina del nervio óptico o el Doppler transcraneal) detectan hallazgos sugestivos de HIC. En todos estos casos el DLE es de elección para el control de la HIC y debe ser considerado la primera medida a realizar (34)(35)(36)(37)(38) .…”
Section: Tratamiento De La Hic Con Cisternas Basales Presentesunclassified
“…Algunos autores, como Manet y colaboradores, agregan a estas condiciones el desarrollo gradual de colecciones subaracnoideas o subdurales localizadas en la cisura de Silvio o interhemisférica, o en los surcos de la convexidad. Esto se basa en el mecanismo fisiopatológico planteado por estos autores como causa de esta situación y que consiste en la denominada hidrocefalia externa (34)(35)(36) .…”
unclassified
“…[6][7][8] Lumbar drain (LD) is one of the simplest, fastest, eff ective, economical methods that removes the blood and helps in the circulation of cerebrospinal fl uid to reduce hydrocephalus. 6,12,13 LD although simple can cause complications which include infection, dislodgement, neurogenic pain, tentorial herniation, syringomyelia, headache and pneumocephalus. 2,9 This study aims to study the outcome of lumbar alone in DH and the author believes that this is the fi rst study to be reported from Nepal.…”
mentioning
confidence: 99%